2019
DOI: 10.1016/j.earscirev.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Glacial history and palaeo-environmental change of southern Taimyr Peninsula, Arctic Russia, during the Middle and Late Pleistocene

Abstract: This Data in Brief paper contains data (including images) from Quaternary sedimentary successions investigated along the Bol'shaya Balakhnya River and the LuktakheUpper TaimyraeLogata river system on southern Taimyr Peninsula, NW Siberia (Russia). Marine foraminifera and mollusc fauna composition, extracted from sediment samples, is presented. The chronology (time of deposition) of the sediment successions is reconstructed from three dating methods; (i) radiocarbon dating of organic detritus (from lacustrine/f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 88 publications
2
51
0
Order By: Relevance
“…The above-lying unit B fluvial sediments were dated to their deposition by Optically Stimulated Luminescence to 42-43 kyr (± 3-4 kyr), which is within the Middle Zyryanka (MIS 3), while redeposited mollusks (P. arctica) within the unit B sediments, eroded from underlying marine unit A, gave ESR ages of 122 and 123 kyr (± 15 kyr). Möller et al, 2019b thus concluded that the unit A marine sediment can be placed with high confidence to their deposition within the Karginsky interglacial (MIS 5e), equivalent to the North West European Eemian. Site BBR 17 is located ∼50 km from the ocean today, but paleoenvironmental reconstructions showed marine inundation of the Taimyr lowlands in front of the retreating ice margin at the transition between the Taz glaciation (MIS 6) and into the Karginsky interglacial (MIS 5e), with sea level at its maximum reaching levels in excess of 80 m above present sea level in this area (Möller et al, 2019b).…”
Section: Samplesmentioning
confidence: 94%
See 4 more Smart Citations
“…The above-lying unit B fluvial sediments were dated to their deposition by Optically Stimulated Luminescence to 42-43 kyr (± 3-4 kyr), which is within the Middle Zyryanka (MIS 3), while redeposited mollusks (P. arctica) within the unit B sediments, eroded from underlying marine unit A, gave ESR ages of 122 and 123 kyr (± 15 kyr). Möller et al, 2019b thus concluded that the unit A marine sediment can be placed with high confidence to their deposition within the Karginsky interglacial (MIS 5e), equivalent to the North West European Eemian. Site BBR 17 is located ∼50 km from the ocean today, but paleoenvironmental reconstructions showed marine inundation of the Taimyr lowlands in front of the retreating ice margin at the transition between the Taz glaciation (MIS 6) and into the Karginsky interglacial (MIS 5e), with sea level at its maximum reaching levels in excess of 80 m above present sea level in this area (Möller et al, 2019b).…”
Section: Samplesmentioning
confidence: 94%
“…Möller et al, 2019b thus concluded that the unit A marine sediment can be placed with high confidence to their deposition within the Karginsky interglacial (MIS 5e), equivalent to the North West European Eemian. Site BBR 17 is located ∼50 km from the ocean today, but paleoenvironmental reconstructions showed marine inundation of the Taimyr lowlands in front of the retreating ice margin at the transition between the Taz glaciation (MIS 6) and into the Karginsky interglacial (MIS 5e), with sea level at its maximum reaching levels in excess of 80 m above present sea level in this area (Möller et al, 2019b). The shells subjected to aDNA analyses were sampled from frozen marine unit A sediment (permafrost) at site BBR 17A and have been kept frozen since the time of collection in 2010 to optimize DNA preservation post-excavation.…”
Section: Samplesmentioning
confidence: 94%
See 3 more Smart Citations